(Table 2, page 1052) Palladium, iridium and gold contents of some oceanic manganese nodules - Robert C Harriss; J H Crocket; M Stainton (PANGAEA, 1968)
The abundance and distribution of palladium, iridium and gold has been determined in manganese nodules from widely varying locations and geological environments within the Atlantic, Indian and Pacific Oceans. The distribution of these metals is characterized by a lack of distinct regional variations, homogeneous distribution within an individual nodule, and a lack of any correlation with variations in major and other trace elements in the nodules. Assuming that all the iridium in the manganese nodules is of extraterrestrial origin, an upper limit on the mass accretion rate of interplanetary matter to the earth is calculated to be 60 tons/day over the surface of the earth.
Supplement to: Harriss, RC et al. (1968): Palladium, iridium and gold in deep-sea manganese nodules. Geochimica et Cosmochimica Acta, 32(10), 1049-1056, https://doi.org/10.1016/0016-7037(68)90107-5